Pola Pemantauan Tumbuh Kembang Anak di Wilayah Pimpinan Ranting Istimewa Aisyiyah, Kampung Bharu Malaysia: Monitoring Patterns of Child Growth and Development in the Area of the Special Branch of Aisyiyah, Kampung Bharu Malaysia - Fauzia, Faurina Risc; Wahyuntari, Evi; Subardjo, Ratna Yunita Setiyani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Nutritional issues are still problematic for developing countries, especially in Southeast ASIA—activities as an effort to improve children's nutritional status. The method is carried out through 3 stages: preparation (coordination with partners, preparation of information media, namely exercise books and videos, TB and BB measuring equipment); Implementation (measurement of BB, TB, and BMI, analysis of nutritional status of children, counseling with experts); and monitoring and evaluation (evaluation of program sustainability). Based on the results of the service carried out, 11 (55%) children were well-nourished, 3 (27.2%) children were overweight, and 7 (35%) children were obese. Education and monitoring of nutritional status are needed for children in the PRIA Kampung Bharu Malaysia area who neglect physical activities and consume balanced nutritional food.